2015
DOI: 10.1016/j.pedneo.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of Serial Neonatal Therapeutic Intervention Scoring System Scores for Short-term Mortality in Very-low-birth-weight Infants

Abstract: The NTISS score at 48 hours seemed to be effective to predict mortality in preterm infants whose birth weight was less than 1500 g. In addition, gestational age played a more important role in predicting mortality than birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…23 Our recently published study demonstrated that the NTISS score at 48 hours can effectively predict mortality in very low birth weight infants. 24 Hsu et al 25 reported bloodstream infections in 793 neonates, and they found that NTISS scores !23 had a higher risk (OR: 6.61, 95% CI: 2.40e26.47) of treatment failure in neonatal bacteremia. In the current study, the NTISS score in the LBW infants with VAP was significantly higher than in those without VAP.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our recently published study demonstrated that the NTISS score at 48 hours can effectively predict mortality in very low birth weight infants. 24 Hsu et al 25 reported bloodstream infections in 793 neonates, and they found that NTISS scores !23 had a higher risk (OR: 6.61, 95% CI: 2.40e26.47) of treatment failure in neonatal bacteremia. In the current study, the NTISS score in the LBW infants with VAP was significantly higher than in those without VAP.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the NTISS, the mean value found (19.9) during the first day of hospitalization did not vary widely than a study carried out to evaluate the severity of critically ill newborns in Ukraine (22.4), as well as compared to other types of studies, showing similarity in the severity and use of interventions in neonatal care in different localities, such as Londrina (17.2), performed with 81 newborns; in Mato Grosso do Sul (18), with 83 newborns; in Mexico (20.4), with 505 newborns; and Taiwan (20.3) with 172 newborns (6,(11)(12)(13)(14) .…”
Section: Discussionmentioning
confidence: 91%
“…Gray and colleagues developed the NTISS while Shah et al developed a score using selected variables derived from the NTISS [ 19 , 32 ]. Seven of the articles reporting external application to new populations used the NTISS [ 33 39 ]. One study used a therapeutic score originally developed for adults, the therapeutic intervention scoring system (TISS) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“… Oygur,2012 [ 38 ] + - + + + - Shah,2015 [ 32 ] + - + + ? + Wu,2015 [ 39 ] + - + + + ? + Limitation present - No limitation ?…”
Section: Resultsmentioning
confidence: 99%